Endothelial Foxp1 Suppresses Atherosclerosis via Modulation of Nlrp3 Inflammasome Activation. Issue 6 (30th August 2019) - Zhuang, Tao; Liu, Jie; Chen, Xiaoli; Zhang, Lin; Pi, Jingjiang; Sun, Huimin; Li, Li; Bauer, Robert; Wang, Haikun; Yu, Zuoren; Zhang, Qi; Tomlinson, Brian; et al.
Abstract : Rationale: Endothelial dysfunction results in sustained and chronic vascular inflammation, which is central to atherosclerotic diseases. However, transcriptional regulation of vascular endothelial inflammation has not been well clarified. Objective: This study aims to explore Foxp (forkhead box P) transcription factor 1 in regulation of endothelial homeostasis, atherogenesis, and its mechanisms. Methods and Results: To assess the importance of Foxp1 in atherosclerosis, Foxp1 expression was analyzed in human coronary artery and mouse artery, and we observed significant downregulation of Foxp1 in atherosclerotic and atherosusceptible endothelium. Endothelial-specific Foxp1 knockout mice ( Foxp1 ECKO ) were bred onto Apoe KO mice to generate endothelial Foxp1-deletion hyperlipidemic model Foxp1 ECKO ;Apoe KO, which displayed significant increases in atherosclerotic lesion formation in aortas and aortic roots with enhanced monocyte adhesion, migration, and infiltration into the vascular wall and formation of inflammatory lipid-laden macrophages. In contrast, endothelial-specific Foxp1 overexpression mice Foxp1 ECTg ;Apoe KO exhibited reduced atherosclerotic lesion formation with less monocyte infiltration. Foxp1 was further identified as a gatekeeper of vessel inflammation by direct regulation of endothelial inflammasome components, including Nlrp3 (NLR [nucleotide-binding and leucine-rich repeat immune receptors] family pyrin domain containing 3), caspase-1, and IL (interleukin)-1β. Moreover, endothelial Foxp1 was found to be regulated by Klf2 (Kruppel-like factor 2). Oscillatory shear stress downregulated Foxp1 expression via repressing Klf2 expression in endothelium, and, therefore, promoted endothelial inflammasome activation, leading to atherosclerotic lesion formation. Simvastatin upregulated the reduced expression of Klf2 and Foxp1 in atherosusceptible vascular endothelium and alleviated vascular inflammation contributing to its inhibitory effect in atherosclerosis. Conclusions: These data are the first in vivo experimental validation of an atheroprotective role of endothelial Klf2 and Foxp1, which reveals a Klf2-Foxp1 transcriptional network in endothelial cells as a novel regulator of endothelial inflammasome activation for atherogenesis, therefore, provides opportunities for therapeutic intervention of atherosclerotic diseases and uncovers a novel atheroprotective mechanism for simvastatin. Visual Overview: An online visual overview is available for this article. Abstract : Supplemental Digital Content is available in the text.